La Historia dell’Europa di Pierfrancesco Giambullari e la “Monarchia universalis”: tra realtà e utopia - VITALI, Francesco (Polis (Bucharest, Romania), 2017)
The Florentine academic Pierfrancesco Giambullari started to write Historia dell’Europa in 1545 at the court of duke Cosimo I de’ Medici. In his Historia, Giambullari analysed the history of the Holy Roman Empire from 887 A.D. to 950 A.D. Above all, he celebrated the advent to the imperial throne of the Saxon Otto I, which was permitted by the Divine Providence. Furthermore, he described the corruption of popes such as Stefano VI and Giovanni XI, who were only focused on extending their temporal power in Italy against the imperial politics. Thus, Giambullari’s admiration for imperial government of Otto I expressed indirectly his approbation of coeval “monarchia universalis” planned by the Hapsburg emperor Charles V. In fact, the duke Cosimo supported the politics of Charles V to contrast his most dangerous enemies: the anti-Medici “fuorusciti”, sustained by France, and pope Paul III. In 1549, when the Florentine duke established a good relationship with the new pope Giulio III and the Italian imperial party collapsed, Giambullari interrupted his writing. So, the realistic hope of “monarchia universalis” evolved into a utopian proposal. Giambullari returned to Historia dell’Europa only when in 1555 Giampietro Carafa, enemy of duke Cosimo, was elected pope as Paul IV. However, in few months Giambullari died and his writing remained unfinished. Although Historia was published in 1566, its perspective of “monarchia universalis” had already been utopian and unrealistic, vis-a-vis the strong alliance formed by duke Cosimo with pope Pio V.